Strategi Meningkatkan Prestasi Akademik dan Literasi Melalui Model BARATA - Listiana, Heni; Rizal, Syaiful; Maimun; Muhlis, Achmad; Yusuf, Achmad (AL MURABBI, 2024)
This research explores the crucial role of literacy in the educational context, with a specific focus on the implementation of the BARATA Literacy Model at SMP Negeri 5 Pamekasan. The primary objective of this study is to investigate the implementation of the BARATA model, related literacy activities, and their impact on students' reading and writing abilities in the school environment. Student participation across different grade levels is delineated, encompassing students from grades 7, 8, and 9. Data regarding students' initial involvement in literacy activities are also identified. The data collection methods involve in-depth interviews with students, the School Principal, and teachers, coupled with observations to gain direct insights into the classroom dynamics during literacy activities using the BARATA model. The research findings indicate that the BARATA model has a positive impact, enhancing students' reading skills, improving academic achievements, and involving the literacy team. Data analysis reveals majority support for the effectiveness of this model, although some respondents express neutral or negative views, emphasizing the importance of understanding variations in perceptions of literacy technology. Furthermore, the data supports the effectiveness of the teacher's validation process for student writings and the initiative to compile students' works into anthology books. Despite variations in responses, the research concludes that the BARATA model has successfully created dynamic literacy activities and positively influenced the literacy competence of students at SMP Negeri 5 Pamekasan.